Optimal Reactive Power Dispatch untuk Meminimalkan Rugi Daya Menggunakan Flower Pollination Algorithm (Jurnal Teknik Elektro, 2019)
This paper presents the Flower Pollination Algorithm (FPA) metaheuristic used to solve the Optimal Reactive Power Dispatch (ORPD) problem. ORPD is a non-linear optimization problem in the electric power system that regulates the generation of reactive power at the generator to minimize the real power loss on the transmission line while maintaining all parameters at the allowable value. In this case the FPA algorithm is used to find the minimum power loss by adjusting the voltage magnitude value of the generator, the transformer tap settings, and the reactive power compensator value in the system while maintaining the magnitude of the bus voltage, active and reactive power at the generator, and the channel capacity remains at its safe limit. ORPD is applied to the IEEE-30 Bus system test consisting of 8 generating units, 4 transformers, 9 reactive power compensators and 41 channels. The system has a load of 283.4 MW and 126.2 MVAR. The results after being optimized using FPA shows the power loss in the channel is reduced to 4,895 MW or reduced by 15.89%. The results of optimization using FPA showed better results compared to Genetic Algorithm and Particle Swarm Optimization.